2009
DOI: 10.1097/cnd.0b013e318190310f
|View full text |Cite
|
Sign up to set email alerts
|

Survival Probabilities of Patients With Childhood Spinal Muscle Atrophy

Abstract: We found a positive trend in the survival of patients with severe SMA. Although we cannot attribute this trend to any single factor, it is likely that advances in pulmonary care and aggressive nutritional support have played a significant role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…Similarly to our study, all of the patients in this study died of respiratory failure or invasive pulmonary infection [6]. In a study by Mammaa et al, the average lifespan of SMA type 1 patients born between 1995 and 2006 is shown to be longer than that of those born between 1980 and 1994, which the authors connect to the increase in use of noninvasive ventilation in SMA patients in the early 1990s [8]. The study by Cobben et al attributes the increase in life expectancy after 1995 to the fact that the medical approach to SMA type 1 patients varies from country to country.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly to our study, all of the patients in this study died of respiratory failure or invasive pulmonary infection [6]. In a study by Mammaa et al, the average lifespan of SMA type 1 patients born between 1995 and 2006 is shown to be longer than that of those born between 1980 and 1994, which the authors connect to the increase in use of noninvasive ventilation in SMA patients in the early 1990s [8]. The study by Cobben et al attributes the increase in life expectancy after 1995 to the fact that the medical approach to SMA type 1 patients varies from country to country.…”
Section: Discussionsupporting
confidence: 69%
“…In our study, none of the patients were on home ventilatory support, and only one relied on gastrostomy tube feeding. In their study, Mannaa et al found the probability of their eight SMA type 1 patients living for 2, 4, and 10 years to be 62%, 62%, and 8%, respectively and linked the increasing lifespan of SMA patients to the increase in respiratory and nutritional support possibilities [8]. Management of these patients with respiratory physiotherapy including assisted cough and chest percussion is showed to limit the risk of respiratory distress requiring invasive mechanical ventilation [7].…”
Section: Discussionmentioning
confidence: 97%
“…Appropriate nutritional management of SMA patients is critical for improving quality of life and optimizing survival,29 although no clear consensus exists on the timing of initiation of nutritional support.…”
Section: Clinical Carementioning
confidence: 99%
“…Accordingly, many SMA patients had nonmucocutaneous candidiasis, which usually only occurs in immunodeficient individuals 25. Moreover, pulmonary infection, especially pneumonia, appears to be a common feature of SMA patients 26, 27, 28, 29, 30. Decreased respiratory efficiency and stasis of secretions can increase risk of infections 29, 31.…”
Section: Potential Functional Consequences Of Lymphoid Organ Defects mentioning
confidence: 99%
“…Moreover, pulmonary infection, especially pneumonia, appears to be a common feature of SMA patients 26, 27, 28, 29, 30. Decreased respiratory efficiency and stasis of secretions can increase risk of infections 29, 31. For this reason, superimposed immunodeficiency has not previously been considered as contributory to the disease etiology but may indeed play a major role in the presentation of chronic pulmonary infection in SMA patients.…”
Section: Potential Functional Consequences Of Lymphoid Organ Defects mentioning
confidence: 99%